The wireless computer networks state recognition over the three-dimensional field of directions - Нестеренко, Сергій Анатолійович; Становський, Андрій Олександрович; Оборотова, Олена Олександрівна (Technology audit and production reserves, 2015)
It is shown that the features of the visual display of the wireless computer networks with partially unavailable monitoring operation elements do not allow detecting their condition by the known intelligent processing methods of static images. It was developed and implemented the method of detection using a three-dimensional field of directions. It was improved method for three-dimensional visual imaging of the structure of partially inaccessible for monitoring damaged wireless computer networks, which is based on the determination of the probability of efficiency inaccessible network elements available from the signals and image processing, the brightness of each pixel is proportional to the corresponding probabilities. It was improved methods of recognizing the visual image of state of the wireless computer network structure by constructing a three-dimensional field of directions for it, and searching the image for the last encoding in a database corresponding to these codes that is recognized as an imprint of the real state of the network. It was performed the test of developed methods in the daily activities of the Intelligence Directorate of Staff of the Land Forces Command of the Armed Forces of Ukraine during the study of features a set of forces and reconnaissance of operational commands and confirmed the possibility of the timely repair and replacement of damaged elements of the wireless network that guarantees the increase in the overall level of efficiency of the latter.